Determinants of Entrepreneurial Intention of Papuan Students (A Study in Universities in Jayapura) - Bharanti, Bonifasia E (Journal of Education and Vocational Research, 2016)
Independent entrepreneurs are urgently needed in developing countries such as Indonesia considering there are many educated unemployed people and limited employment, especially in formal sector, and increasing number of job seekers every year. The common phenomenon in Papua is business opportunities in the economic sector are often used by migrants who work in formal and informal sectors, while local working age Papuans, especially university graduates, are less interested to be economic agents in Papua. This study aimed to discover factors which drove and improved entrepreneurial intention of Papuan students based on their personality characteristics: self-efficacy and need for achievement; formal environmental factors such as Entrepreneurship education and socio-cultural factor which was culturally-formed gender stereotypes. The research design was explanatory research with samples collected by stratified random sampling technique and the samples were 197 students from 4 universities in Jayapura. The data collection technique used questionnaires and data was analyzed by difference test and path analysis. The research result showed (1) Female students have stronger entrepreneurial intention, motivation for achievement, and self-efficacy than male students. (2) Partially, everything had direct influence on the formation of entrepreneurial intention except for entrepreneurship education